2021
DOI: 10.3390/ani12010010
|View full text |Cite
|
Sign up to set email alerts
|

Abortion and Lamb Mortality between Pregnancy Scanning and Lamb Marking for Maiden Ewes in Southern Australia

Abstract: The contribution of abortions to the overall mortality of lambs born to maiden (primiparous) ewes in Australia remains unclear. This cohort study aimed to quantify abortion and lamb mortality for ewe lambs and maiden Merino two-tooth ewes. Lamb mortality from pregnancy scanning to marking were determined for 19 ewe lamb and 11 Merino two-tooth ewe flocks across southern Australia. Average lamb mortality from scanning to marking was 35.8% (range 14.3–71.1%) for the ewe lambs and 29.4% (range 19.7–52.7%) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 41 publications
6
25
1
Order By: Relevance
“…The difference in reproductive rate between these age groups was less than other studies, which have ranged from 75 to 124% [ 7 , 14 ], whereas the difference in lamb survival between these age groups tended to be greater than most other studies where the difference was less than 10% [ 14 , 17 , 18 , 19 ]. The wider variation in marking rate, reproductive rate and lamb survival between individual flocks of non-Merino ewe lambs was similar to these and other studies, including Clune et al [ 9 ] and Thompson et al (unpublished data). Improved understanding of the degree of variation and causes of poorer reproductive rate and lamb survival in maiden ewes will inform extension and adoption programs to improve maiden ewe reproductive performance.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The difference in reproductive rate between these age groups was less than other studies, which have ranged from 75 to 124% [ 7 , 14 ], whereas the difference in lamb survival between these age groups tended to be greater than most other studies where the difference was less than 10% [ 14 , 17 , 18 , 19 ]. The wider variation in marking rate, reproductive rate and lamb survival between individual flocks of non-Merino ewe lambs was similar to these and other studies, including Clune et al [ 9 ] and Thompson et al (unpublished data). Improved understanding of the degree of variation and causes of poorer reproductive rate and lamb survival in maiden ewes will inform extension and adoption programs to improve maiden ewe reproductive performance.…”
Section: Discussionsupporting
confidence: 89%
“…The 58% difference in marking rate for non-Merino ewe lambs compared with multiparous ewes across 40 farms in our study was similar to the difference recently reported from nine commercial farms representing more than 300,000 records in New Zealand (72 vs. 142%) [ 14 ]. Likewise, marking rate was more variable between flocks for non-Merino ewe lambs compared with multiparous non-Merino ewes, with the overall average and variation in marking rate between flocks of non-Merino ewe lambs being similar to results reported by both Shorten et al [ 14 ] and Clune et al [ 9 ]. The 22% difference in marking rate for Merino two-tooth ewes compared to multiparous ewes across 39 farms was greater than the differences measured by Kleemann and Walker [ 10 ] on 14 farms in South Australia (70 vs. 86%) and a recent survey of 1200 Merino producers across Australia (79 vs. 93%) [ 15 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations